Use Of Multimedia Technologies In Primary Classes - Janar Qabilbekova Abdullayevna (Euro Asian Journal Publishing, 2024)
Effective use of modern computer and information technologies is considered the main factor in improving the quality and effectiveness of primary education today
Keywords: Multimedia; schools; speed of information; aspiring